Phytochemicals as Potential Curative Agents against Viral Infection: A Review - Kumar, Abhijeet; Singh, Anil K.; Tripathi, Garima (Current Organic Chemistry, 2020)
The present pandemic erupted due to highly contagious coronavirus SARS-CoV- 2, and lack of any efficient therapy to restrain its infection and treatment, led the scientific community to re-evaluate the efficacy of commonly available phytochemicals as potential therapeutic agents. The vast pharmacological activities and medicinal significance of the plant-derived natural products against a diverse range of physiological disorders and diseases are well documented. Under the current health emergency across the world, there is an urgent requirement of repurposing of the available FDA approved drugs and natural products which could help in controlling the infections and alleviating the severity of the diseases as discovering entirely new chemical entity as a novel drug would be a protracted and costly journey. Some of the phytochemicals have already displayed potential anti-viral activity against different targets of SARS-CoV-2 virus. The present review would provide an account of the prevalent phytochemicals with antiviral activities, which would help in the development of promising drug therapy for the treatment of COVID-19 and similar such highly infectious viruses.
Keywords: terpenoids